Silicate solubilizing bacteria UPMSSB7, a potential biocontrol agent against white root rot disease pathogen of rubber tree - Shabbir, Imran; Abd Samad, Mohd Yusoff; Othman, Radziah; Wong, Mui-Yun; Sulaiman, Zulkefly; Md Jaafar, Noraini; Bukhari, Syed Asad Hussain (Springer, 2020)
Rigidoporus microporus is a causal agent of white root rot disease of rubber trees. Chemical control is commonly used against this disease but it is expensive, causes environmental pollution and fungal resistance. Silicon is a beneficial element which enhances plant growth and disease resistance but mostly present in insoluble forms. Silicate solubilizing bacteria (SSB) can solubilize the insoluble forms of silicates. This study aimed to screen and evaluate potential SSB with solubilizing activity, plant growth promoting traits and antagonistic activity against R. microporus. Bacteria were isolated from healthy rubber plantation area. Five out of 26 bacterial isolates which showed the ability to solubilize silicate on magnesium trisilicate media were screened in vitro for growth promoting traits and production of indole-3-acetic acid (IAA), siderophores and hydrolytic enzymes. The investigation of antagonistic activity against R. microporus was conducted using dual culture test. The potential SSB isolates were identified by 16S rRNA gene sequencing. The isolate UPMSSB7 showed the highest solubilization of silicate, phosphate (P) and potassium (K) (solubilizing index 4.67, 2.52 and 2.61, respectively). It also showed highest silicate solubilization at 5 and 10 days (9.76 and 11.55 mg L−1, respectively) in liquid assay. It strongly inhibited the growth of R. microporus with percent inhibition of radial growth of 57.24% and produced highest IAA (19.96 µg mL−1). All the isolates produced siderophores. Two isolates, UPMSSB7 and UPMSSB10, were able to secrete cellulase enzyme, but pectinase was produced by UPMSSB7 only. The isolate UPMSSB7 was identified as Enterobacter sp. This isolate was found to be the most potent antagonistic isolate against R. microporus and simultaneously the most efficient one in solubilizing insoluble silicates, as well as P and K.